PENGELOLAAN ANGGARAN PEMILIHAN KEPALA DAERAH PADA KOMISI PEMILIHAN UMUM KOTA PALU TAHUN 2015 - Zatriawati, Zatriawati (Katalogis, 2017)
This research intends to analyze the budget management of regional head election performance based on the year of 2015. The reseach was conduted in General Election Commission Office Palu using descriptive qualitative method. The research results indicate that budget of major and the vice major election Palu 2015 was managed well and proportional. General election commision palu also succeeds in applaying performance based budget on the mayor and the vice major election Palu in 2015.